An investigation of protein variation in Ulva lactuca and Ulva rigida under high nitrogen culture conditions - Wilkinson, Sarah (Department of Biological Sciences, 2017)
In the light of findings that abalone achieve higher growth rates when fed on high protein diets, this study attempts to increase the protein content of two macroalgae under culture conditions. Ulva lactuca and U rigida were grown in saturating NH₄⁺ - N (1 mM) and PO₄³⁻P (70 μM ) concentrations. Of the two, protein levels of U. lactuca showed the greatest increase over time. Natural populations had a content of 3.7 % of dry weight. This increased significantly (p <0.05) to a maximum value of 4.5 % after 8 days growth in nutrient enriched conditions. The protein content of U. rigida increased significantly from 3.3 % to 3.9 % after 6 days of growth in nutrient enriched conditions. An interspecies comparison was made using the intertidal species Porphyra capensis, Ulva capensis and Gracilaria gracilis. The highest protein content was found in P. capensis (11.5 %), followed by U capensis (3.0 %) and G. gracilis (2.7 %). Results indicate the suitability of P. capensis as a high-protein abalone fodder. Furthermore, results suggest that the protein content of abalone fodder may be optimized under aquaculture conditions.